A systematic review of clinical applications of polymer gel dosimeters in radiotherapy. (January 2019) - Farhood, Bagher; Geraily, Ghazale; Abtahi, Seyed Mohammad Mahdi
Abstract: Radiotherapy has rapidly improved because of the use of new equipment and techniques. Hence, the appeal for a feasible and accurate three-dimensional (3D) dosimetry system has increased. In this regard, gel dosimetry systems are accurate 3D dosimeters with high resolution. This systematic review evaluates the clinical applications of polymer gel dosimeters in radiotherapy. To find the clinical applications of polymer gel dosimeters in radiotherapy, a full systematic literature search was performed on the basis of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines in electronic databases up to January 31, 2017, with use of search-related terms in the titles and abstracts of articles. A total of 765 articles were screened in accordance with our inclusion and exclusion criteria. Eventually, 53 articles were included in the study. The findings show that most clinical applications of polymer gel dosimeters relate to external radiotherapy. Most of the gel dosimeters studied have acceptable dose accuracy as a 3D dosimeter with high resolution. It is difficult to judge which is the best polymer gel dosimeter to use in a clinical setting, because each gel dosimeter has advantages and limitations. For example, methacrylic acid–based gel dosimeters have high dose sensitivity and low toxicity, while their dose response is beam energy dependent; in contrast, N -isopropylacrylamide gel dosimeters have low dose resolution, but their sensitivity is lower and they are relatively toxic. Highlights: Most polymer gel dosimeters have acceptable dose accuracy. Acrylamide-based gel dosimeters are highly toxic. The dose response of methacrylic acid–based gel dosimeters is beam energy dependent. The sensitivity of N -isopropylacrylamide gel dosimeters is lower. It is difficult to judge which is the best polymer gel dosimeter to use in the clinic.